Optimal bidding and offering strategies of merchant compressed air energy storage in deregulated electricity market using robust optimization approach - Nojavan, Sayyad; Najafi-Ghalelou, Afshin; Majidi, Majid; Zare, Kazem (Energy (Oxford), 2018)
Nowadays, severe uncertainty of electricity market price is a challenge issue in power systems that market players are faced. As one of market players, merchant compressed air energy storage system can be studied to investigate how energy is purchased/sold in the presence of electricity market price uncertainty. Therefore, this paper proposes, robust optimization approach is employed to achieve the offering and bidding curves of compressed air energy storage which should be submitted to the pool market. In the proposed method, the minimum and maximum amounts of electricity market prices are considered instead of the forecasted prices which allows formulating a collection of robust mixed-integer linear programming problem problems. The offering and bidding curves of compressed air energy storage are obtained based on sufficient data from results of these problems to be offered to the market operator. A case study is used to show the performance of proposed method. •Compressed air energy storage (CAES) system is considered in electricity market.•Optimal operation of CAES is optimized to determine the charge and discharge decision.•Uncertainty model of electricity market price is considered in the proposed model.•Electricity market price uncertainty is modeled using robust optimization approach.•Offering and bidding curves of CAES obtained based on robust optimization approach.